Wildlife road mortalities during COVID-19 pandemic-related lockdown in south Texas: a comparative survey - Beer, Bradley E.; Ryer, Kevin; Rahman, Md Saydur; Young, John H.; Kline, Richard J. (Frontiers in Ecology and Evolution, 2025)
Mortalities of wildlife caused by collisions with vehicles along roads are increasing in prevalence, threatening the existence of various species and populations. The COVID-19 pandemic-related lockdown provided an opportunity to gain a better understanding of how wildlife vehicle mortality occurrences change in response to anthropogenic variables and how varying survey methods influence obtaining mortality data. In this study, data were collected in three observation periods: pre-lockdown (PreL), during lockdown (DL), and post-lockdown (PostL) in south Texas. There were 194 wildlife mortalities recorded during weeks 4–27 of 2020. Results of this study showed that road mortality survey counts did not change PreL, during COVID-19 pandemic-related lockdown (i.e., DL), and PostL. This study also investigated number of mortality survey observers, a key element in road mortality surveys. We observed that two observers detected more wildlife road mortalities than one observer. Information on these novel findings would be useful in the wildlife road mortality survey methods in the future.